Penerapan Kode Etik Notaris Dalam Permasalahan Yang Terjadi Di Pelaksanaan Praktik Notaris - Riva Raditya; Kholis Roisah (Magister Kenotariatan Universitas Diponegoro, 2022)
Notaries in carrying out their profession must be based on law Number 2 of 2014 and the Notary Code of Ethics. The purpose of writing this journal is to find out the problems that often occur regarding violations of the Notary Code of Ethics and the implementation of the Notary's Code of Ethics in Notary practice. The research method used is Normative. The results of the discussion of this journal are problems that usually occur in violations of the Notary Code of Ethics, namely the installation of a nameplate outside the scope of the office, promotions by sending condolences or congratulations, and determining honoraria that are not in accordance with the association agreement or the Notary's Code of Ethics, the second application of the Code. Notary ethics is not maximal due to lack of firmness and monitoring from the Honorary Council and the Supervisory Board in carrying out their duties. The conclusion from this journal is that the problems that often occur in the Notary Code of Ethics, namely the installation of name boards, congratulations and sorrows and determination of honoraria, the application of the Notary Code of Ethics is considered less than optimal and less effective.Keywords: notary; practice; notary code of ethicsAbstrakNotaris dalam melaksanakan profesinya harus berdasarkan Undang-Undang Nomor 2 Tahun 20l4 dan Kode Etik Notaris. Tujuan penulisan jurnal ini adalah untuk mengetahui permasalahan yang sering terjadi terkait pelanggaran Kode Etik Notaris dan pelaksanaan penerapan Kode Etik Notaris dalam praktik Notaris. Metode penelitian yang digunakan yaitu Normatif. Hasil pembahasan jurnal ini adalah permasalahan yang biasa terjadi dalam pelanggaran Kode Etik Notaris yaitu pemasangan papan nama di luar lingkup kantor, promosi dengan mengirimkan ucapan duka cita atau ucapan selamat, serta penetapan honorarium yang tidak sesuai dengan kesepakatan perkumpulan atau Kode Etik Notaris, kedua penerapan Kode Etik Notaris kurang maksimal karena kurang tegasnya dan pemantauan dari Dewan Kehormatan serta Majelis Pengawas dalam menjalankan tugasnya. Simpulan dari jurnal ini yaitu permasalahan yang sering terjadi dalam Kode Etik Notaris yaitu pemasangan papan nama, ucapan selamat dan duka serta penetapan honorarium, penerapan Kode Etik Notaris dinilai kurang maksimal dan kurang efektif.Kata kunci: notaris; penerapan; kode etik notaris